Predictors of Prediabetes Among Young Adults in East Java of Indonesia: A Cross-sectional Study - Pratiwi, Ika Nur; Widyawati, Ika Yuni; Nursalam, Nursalam; Pawanis, Zulfayandi; Qonaah, Arina; Lee, Bih-O (Nurse Media Journal of Nursing, 2024)
Background: Prediabetes is a condition that can be controlled and managed to prevent the occurrence of type 2 diabetes mellitus (T2DM). This condition can occur at all ages, especially in young adults. However, little is known about what factors increase the risk of prediabetes in young adults in East Java, Indonesia.Purpose: This study aimed to estimate the prevalence and the influential risk factors of prediabetes among young adults in East Java, Indonesia.Methods: This study used a cross-sectional design. The purposive sampling technique was used to recruit young adults in East Java Province, Indonesia. International physical activity questionnaire short-form version questionnaire (IPAQ-SF) and physical indicators for anthropometry were used to obtain data on sociodemographic characteristics, prediabetes knowledge, and physical activity. In addition, blood pressure, impaired fasting glucose (IFG), and body mass index (BMI) were measured. Multivariable logistic regression was employed in the analysis to determine risk factors associated with prediabetes.Results: There were 126 participants recruited, with 69 (54.8%) having prediabetes based on IFG levels. Age (p=0.035), regular exercise (p=0.015), activity level (p=0.026), body weight (p=<0.001), waist circumference (p=0.002), BMI (p=<0.001) and obesity (p=<0.001) were significant factors associated with prediabetes.Conclusion: The high prevalence of prediabetes in young adults is associated with age, routine exercise, activity level, body weight, waist circumference, BMI and obesity. It is crucial to implement strategies, such as regular IFG testing, to identify young adults with these risk factors for prediabetes screening.